An ethnobotanical study of medicinal plants among the Dusun Liwan community along the downstream Miroli river, Ranau, Sabah / Eva Olivia Johnius - Johnius, Eva Olivia (Universiti Teknologi MARA, Sabah: Kota Kinabalu Campus, 2017)
This study is about the ethnobotanical study of the medicinal plants that were used to treat diseases by Dusun Liwan communities along the downstream of Miroli River, Ranau, Sabah. This study is conducted by collecting and recording the data by interviewing Dusun Liwan medicine man, and knowledgeable persons with the help of semi-structured and open ended questionnaire. The data that were documented are listed along with their indication, part used, form of preparation and route of administration. Then the samples (claimed medicinal plant) were taken for further identification species. The results then further analysed in order to determine Informant Consensus Factor (ICF) of the plants on the basis of their use under various ailment categories. From the result, 84 medicinal plants species from 50 families used for the treatment of 19 different ailments categories were collected. The most frequently plant part used is leaves (32.22%) while decoction is the major form of preparation which is 46 percent. In second objective, the dichotomous key of 84 medicinal plants consist of 1 Kingdom (plantae), 1 Division (Magnoliophyta, 4 Class (Equisetopsida, Liliopsida, Lycopodiopsida and Magnoliopsida), 11 Sub-class, 34 Order and 50 Family and 79 Genus and 84 species. For the third objective, the quantitative analysis of Informant Consensus Factor (ICF) showed that the local people tend to agree more to each other in the term of plants used to treat skeletal muscular system disorder and chicken pox (1.00 each). Ocotomeles sumatrana Miq. and Imperata cylindrical (L.) P. Beauv. are the medicinal plant species that claimed by the local people in treating skeletal muscular system disorder and chicken pox which showed ICF values of 1.00 because the informants agreed of using only a single species in this category. This study could open an avenue for future pharmacological research works, or serve as reference especially for future quantitative ethnobotanical investigations among indigenous groups all over the Sabah, Malaysia.